STRUCTURAL CHARACTERISTICS AND PLANT SPECIES DIVERSITY OF SOME NATURAL FOERST TYPES AT PHOU KHAO KHOUAY NATIONAL PARK, LAO PEOPLE’S DEMOCRATIC REPUBLIC - Chanthalaphone, Keovilay; The Doi, Bui; Xuan Truong, Le; Van Tu, Nguyen (Journal of Forestry Science and Technology, 2020)
Phou Khao Khouay National Park (PKKNP) is one of the 24 National Parks and protected areas in Lao People’s Democratic Republic (Lao PDR) that supports high biodiversity. The tree and seedling layers of natural forest in Thaphabat was represented 76 species belonging 42 families. The largest family was Dipterocarpaceae (9 species), followed by Fabaceae (5 species) and Rubiaceae (4 species). Species in terms of individual number were Hydnocarpus ilicifolia, Hopea spp. and the largest families in terms of species number were Rubiaceae and Dipterocarpaceae. Diversity was found very high in four forest types, the Menhinick’s Richness ranged from 2.07 to 2.95. The Simpson index ranged from 1.43 to 1.62. The Shannon index ranged from 0.93 to 0.97. The largest tree height and maximum mean diameter (D1.3) belong to the family of Dipterocarpaceae. Compared similarity index between seedling and tree species at four forest types were that, the average forest has the highest percentage of species common (76.58%). The lowest was in the extremely poor forest (47.66%).